Sex as a Biological Factor in the Changes in Disease Patients During Ramadan Intermittent Fasting: A Systematic Review - Roky, Rachida; Aadil, Nadia; Krami, Al Mehdi; Benaji, Brahim; Errabih, Ikram; Abdelrahim, Dana N.; Faris, MoezAlIslam Ezzat (Frontiers in Nutrition, 2022)
Background: During Ramadan, many patients with diabetes, renal, cardiovascular, gastrointestinal diseases, headaches, and epilepsy choose to fast even against their doctor’s advice. The impact of this intermittent fasting on health and disease could be different in men and women. The aim of this study was to determine the effect of sex as a factor in diseases outcomes of patients who opt to fast during Ramadan. Main body: The articles included in this study reported data on six diseases: diabetes, renal, cardiovascular, gastrointestinal diseases, headaches, and epilepsy. A systematic search was performed on PubMed and Scopus for observational and clinical studies mentioning Ramadan, diabetes, renal, cardiovascular, gastrointestinal diseases, headaches, and epilepsy in both men and women. Data was extracted by two independent reviewers using a standardized data-collection form. From 381 original articles, 38 studies were selected, including 25023 patients of which 44.4% were women. Sex-based differences were reported by 18 studies for several variables such as body mass index, blood glucose, the frequency of hypoglycemia, renal colic, mortality, thrombosis, and gastrointestinal diseases in patients fasting during Ramadan. Most of the differences between men and women were reported both in the baseline period before Ramadan and during Ramadan. Indeed, during the period outside Ramadan, the frequency of renal colic, cardiovascular, gastrointestinal diseases, were higher in men; while body mass index, Thrombosis, and headache were higher in women. In the remaining 21 studies, it was reported that the sex factor was not associated with the effect of Ramadan fasting in the frequency and other outcomes of these diseases. Conclusion: Currently, small attention is paid to sex as a determinant factor in patients while fasting during Ramadan. There appeared to be differences in the frequency and incidence of diseases in men and women during Ramadan. Closer attention to sex differences regarding the frequency and the progression of the diseases during fasting may help to improve patient care, especially to benefit those patients willing to fast during Ramadan.